2022
DOI: 10.1038/s41467-022-28291-y
|View full text |Cite|
|
Sign up to set email alerts
|

Characterising within-hospital SARS-CoV-2 transmission events using epidemiological and viral genomic data across two pandemic waves

Abstract: Hospital outbreaks of COVID19 result in considerable mortality and disruption to healthcare services and yet little is known about transmission within this setting. We characterise within hospital transmission by combining viral genomic and epidemiological data using Bayesian modelling amongst 2181 patients and healthcare workers from a large UK NHS Trust. Transmission events were compared between Wave 1 (1st March to 25th July 2020) and Wave 2 (30th November 2020 to 24th January 2021). We show that staff-to-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…In addition, on AMU there were likely longer stays of asymptomatic/ paucisymptomatic cases prior to universal PPE use, more fomites (e.g. bedside tables, chairs), and more frequent interspeciality interactions resulting in transmission between HCWs 37 . In the event of a further wave or outbreak, infection prevention and control (IPC) interventions to reduce risk in these areas could include targeted IPC training and auditing (particularly of PPE use and break areas), serial staff testing, pop-up isolation units in bay areas and optimising staff-to-patient ratios.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, on AMU there were likely longer stays of asymptomatic/ paucisymptomatic cases prior to universal PPE use, more fomites (e.g. bedside tables, chairs), and more frequent interspeciality interactions resulting in transmission between HCWs 37 . In the event of a further wave or outbreak, infection prevention and control (IPC) interventions to reduce risk in these areas could include targeted IPC training and auditing (particularly of PPE use and break areas), serial staff testing, pop-up isolation units in bay areas and optimising staff-to-patient ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found conflicting evidence on this point. Caring for COVID-19 patients was found not to increase risk of infection in 2 large studies conducted in the USA [4,19], whereas in the UK, those working in patient-facing roles during the pandemic have been shown to be at higher risk of infection [3,16], and occupational exposure to patients and colleagues with COVID-19 has been shown to increase the risk of HCW infection in UK settings [20,21]. It should be noted that there are different PPE standards recommended by the 2 countries.…”
Section: Plos Medicinementioning
confidence: 99%
“…Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, 1 there have been reports of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission to patients and healthcare workers (HCW) within healthcare facilities. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Factors contributing to these outbreaks have included patient accommodation in multibed rooms or bays, [6][7][8]11,12,17 lack of infection prevention and control precautions due to failure to identify patients admitted with or incubating SARS-CoV-2, [6][7][8][9][10]20 and nosocomial exposure to a patient with COVID-19. [15][16][17][18][19][20] Rhee et al 22 demonstrated that consistent application of infection prevention and control measures can reduce or prevent the spread of SARS-CoV-2 in healthcare settings.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Factors contributing to these outbreaks have included patient accommodation in multibed rooms or bays, [6][7][8]11,12,17 lack of infection prevention and control precautions due to failure to identify patients admitted with or incubating SARS-CoV-2, [6][7][8][9][10]20 and nosocomial exposure to a patient with COVID-19. [15][16][17][18][19][20] Rhee et al 22 demonstrated that consistent application of infection prevention and control measures can reduce or prevent the spread of SARS-CoV-2 in healthcare settings. However, outbreaks in healthcare facilities continue.…”
mentioning
confidence: 99%